When and How Slow Motion Makes Products More Luxurious - Jung, SungJin; Dubois, David (Journal of Marketing Research, 2023)
This research examines when and how the speed of video ads influences consumers’ perceptions of luxuriousness and their subsequent behaviors toward products or brands featured in the ads. Across 12 experiments (total N = 27,227, five preregistered), the authors demonstrate that when a video ad depicts a product in slow motion (vs. regular speed), consumers perceive the featured product or brand as more luxurious. The effect emerges across various product categories (chocolate, shampoo, mineral water, wine) and in different countries (United States, United Kingdom, France). Tests of mediation and moderation suggest that the effect occurs because viewing a slow-motion ad increases feelings of immersion, which lead consumers to expect greater hedonic value from the featured product and thus view it as more luxurious. Consistent with this account, the effect weakens when video blurriness or buffering impairs the immersive viewing experience afforded by slow motion, and the effect attenuates among consumers who are very weakly or very strongly predisposed to experience immersion. Finally, by enhancing perceptions of luxuriousness, slow motion subsequently boosts consumers’ desire for the featured product or brand (as manifested by higher willingness to pay, purchase intentions, and ad click rates), particularly when the goal to consume luxury is salient (vs. not).